Coastal Upwelling Under Anthropogenic Influence Drives the Community Change, Assembly Process, and Co‐Occurrence Pattern of Coral Associated Microorganisms. Issue 2 (13th February 2023) - Zhu, Wentao; Liu, Xiangbo; Zhu, Ming; Xia, Jingquan; Chen, Rouwen; Li, Xiubao
Abstract: Summer upwelling areas may serve as a thermal refuge for coral reefs under climate change, and the environmental adaptation of scleractinian coral to upwelling environments remains to be further understood. In this work, we systematically analyzed how the coral holobionts of Galaxea fascicularis respond to different environments between the Qiongdong upwelling and non‐upwelling regions. The presence of colder and more saline water was found in seasonal upwelling region east of Hainan Island. Compared with the corals in the non‐upwelling environment, the corals from the upwelling environment generally had higher Symbiodiniaceae density, tissue biomass, and protein content. Evident spatial differences existed in Symbiodiniaceae composition among different regions, and the corals in the upwelling region had remarkably higher symbiont diversity. Importantly, the coastal upwelling under anthropogenic influence (i.e., nutrient pollution and coastal development) shaped coral bacterial communities significantly and decreased their diversity. Local adaptations of coral to environmental changes can be inferred from the flexibility and ecological functions of the coral core microbiome. In particular, the coastal upwelling environment led assembly of coral‐associated bacteria more deterministic rather than stochastic. In the upwelling region, microbial co‐occurrences had more positive interactions but the ecological network structure had a lower stability. These findings deepen the understanding of the ecological impact of upwelling on coral adaptation in the Anthropocene. Plain Language Summary: With the progress of global climate change, the frequency and severity of coral bleaching are expected to increase significantly. Fortunately, upwelling exposes corals to cool and nutrient‐rich waters, thereby helping to reduce the thermal impacts of climate change and serving as a potential thermal refuge. We investigated and sampled in coral reefs with different environmental gradients, including upwelling and non‐upwelling in Hainan Island. The Galaxea fascicularis samples from the upwelling region exhibited better coral physiological parameters (higher values of Symbiodiniaceae density, tissue biomass, and protein content). In addition, upwelling changed the diversity and structure of the coral microbiota (microalgal endosymbionts and bacteria) significantly. Coral hosts could act as filters for microorganisms, allowing certain microbial taxa to colonize or persist and selecting the most favorable and beneficial microbiome in a specific environment. Upwelling habitats might promote positive cooperation and simple interaction between bacterial communities associated with the coral host, which is crucial for the acclimatization of the holobiont to quickly respond to environmental changes. This study provides detailed analysis of how coral responds to the summer upwelling environment from a microbial perspective. Key Points: Galaxea fascicularis in upwelling under anthropogenic influence suggested high physiological plasticity and symbiont specificity Microbiome flexibility facilitated local acclimatization of coral holobiont by readily responding to the upwelling environment Upwelling promoted bacterial assembly more deterministic, but reduced the complexity and stability of the microbial network